A Behavioral Model of Work-trip Mode Choice in Shanghai - Gang Liu (Statistics Norway, Research Department, 2006)
This paper analyzes travelers' choice behavior by using data from a stated preference survey on work-trip mode choice in Shanghai. Several versions of a multinomial choice model are specified and estimated. According to the estimation results the utility function with money cost divided by income adjusted by an equivalence scale is chosen as the preferred model. Based on the estimation results from the preferred model, value of time, elasticities of aggregate mode choice with respect to income, cost, travel and waiting time, are computed. The conditional elasticities given low, middle and high adjusted income levels are calculated and discussed as well. The results obtained may be useful for transportation policy makers in Shanghai.
Keywords: C25; C42; C52; R41; 330; work-trip mode choice; stated preference survey; multinomial choice model; choice probability and elasticity